Autistic undergraduate students' transition and adjustment to higher education institutions. (November 2021) - Kim, So Yoon; Crowley, Shannon; Bottema-Beutel, Kristen
Highlights: Many autistic college students negatively described their transition experience. Proximity to home, social support, and transition programs helped the transition. They struggled with new expectations, social difficulties, and practical issues. Students felt adjusted after initial difficulties during the transition period. Familiar routines and positive academic/social experiences made them feel adjusted. Abstract: Background: Only a limited number of studies have specifically examined autistic undergraduate students' perspectives on transition. Positive experiences during the initial transition from high school to college lead to long-term success in college. Method: This study examined the transition and adjustment experiences of 27 autistic undergraduate students attending higher education institutions (HEIs) in the United States. Semi-structured interviews were analyzed using qualitative content analysis. Results: The majority (66.7 %) of participants described the transition experience in negative terms. They also reported that geographical proximity to home and family support, social relationships, transition programs, structural changes from their high school experiences, and logistic difficulties were important aspects of their transition experiences during the first few months of HEI. All participants indicated they felt adjusted to college life at the time of the interview, and adjustment was facilitated by familiarity with campus routines, academic achievement, and positive social experiences. Conclusions: Themes associated with autistic students' transition and adjustment experiences should be followed-up in future quantitative research. Careful transition planning that informs autistic students about expectations associated with HEI, familiarizes them with college life, helps them gain practical skills needed in colleges (e.g., transportation), and helps them find a balance between parental support and independence is needed to support autistic students through transition and adjustment.